2019
DOI: 10.1017/hpl.2019.18
|View full text |Cite
|
Sign up to set email alerts
|

Fabrication of kW-level chirped and tilted fiber Bragg gratings and filtering of stimulated Raman scattering in high-power CW oscillators

Abstract: Suppression of stimulated Raman scattering (SRS) by means of chirped and tilted fiber Bragg gratings (CTFBGs) has become a key topic. However, research on high-power systems is still lacking due to two problems. Firstly, after the inscription, there are a large number of hydroxyl compounds and hydrogen molecules in CTFBGs that cause significant heating due to their strong infrared absorption. Secondly, CTFBGs can couple Stokes light from the core to the cladding and the coating, which causes serious heating in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
32
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 39 publications
(32 citation statements)
references
References 23 publications
(28 reference statements)
0
32
0
Order By: Relevance
“…Chirped fiber Bragg gratings (CFBGs) are an alternative, but in many fabrication systems it was difficult to obtain such structures with high reflectance and low FWHM values until recently. Nowadays there are new techniques and possibilities to achieve CFBGs with high reflectance and low FWHM values [ 27 , 28 , 29 ]. Hence, their use in interrogation systems is problematic.…”
Section: Analysis Of the Obtained Results And Discussionmentioning
confidence: 99%
“…Chirped fiber Bragg gratings (CFBGs) are an alternative, but in many fabrication systems it was difficult to obtain such structures with high reflectance and low FWHM values until recently. Nowadays there are new techniques and possibilities to achieve CFBGs with high reflectance and low FWHM values [ 27 , 28 , 29 ]. Hence, their use in interrogation systems is problematic.…”
Section: Analysis Of the Obtained Results And Discussionmentioning
confidence: 99%
“…Figure 4c shows the temperature image recorded by a thermal camera when laser power was 1935 W. It can be seen that the temperature distribution along the CTFBG is relatively uniform, and the maximum value is about 52 • C with a thermal slope of~0.015 • C/W. The thermal image indicated there are no defects along the CTFBG, and the heat should be mainly caused by the inscription technology, as well as residual hydrogen and -OH-related chemical bonds [22].…”
Section: Fabrication Of High-power Ctfbgsmentioning
confidence: 99%
“…The typical index modulation depth was 10 −3 , and the spectral shape indicated that its uniformity over the grating length of 35 mm was fine. After inscription, the grating needs further post-processing to release the thermal stress and remove the residual hydrogen, which will cause a large amount of heat while operating [22]. After step annealing and packaging, this CTFBG can operate at 2 kW power level.…”
Section: Fabrication Of High-power Ctfbgsmentioning
confidence: 99%
See 1 more Smart Citation
“…Then, they used cascading multiple CTFBGs to suppress SRS in a 5-kW fiber laser [18][19][20] . In 2019, we enabled CTFBG to work well at over 1-kW laser power and applied it to suppress SRS in a kilowattlevel continuous-wave (CW) fiber laser whose SRS was suppressed by 99.5% [21] . Similarly, LPFGs can suppress SRS by coupling the Raman scattered light from forwardpropagating core modes to forward-propagating cladding modes.…”
Section: Introductionmentioning
confidence: 99%